2018
DOI: 10.1021/acssuschemeng.8b05653
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Oxide Post-Treatment for Enhanced Photovoltage of Printable Perovskite Solar Cells

Abstract: Printable perovskite solar cells (PSCs) have attracted widespread attention due to the simple fabrication process and low-cost raw materials. However, because no hole transport material is used and the carbon layer possess a relatively low work function of only 4.8–5.0 eV, a significant potential loss exists in printable PSCs, resulting in a relatively low open-circuit voltage (V OC). We employed vanadium oxide (VO x ) to post-treat the interface of carbon/perovskite, and effectively enhanced the photovoltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…have been employed in the perovskites for reducing the defect density and improving the charge transportation, [ 18,20,21 ] and various strategies have been developed to increase the work function of the carbon electrodes. [ 22,23 ] These approaches have been proved effective for enhancing the photovoltage of triple‐mesoscopic PSCs. At the same time, it is found that suppressing the charge recombination at the perovskite/carbon interface plays a significant role for fabricating devices with high V OC and PCE.…”
Section: Introductionmentioning
confidence: 99%
“…have been employed in the perovskites for reducing the defect density and improving the charge transportation, [ 18,20,21 ] and various strategies have been developed to increase the work function of the carbon electrodes. [ 22,23 ] These approaches have been proved effective for enhancing the photovoltage of triple‐mesoscopic PSCs. At the same time, it is found that suppressing the charge recombination at the perovskite/carbon interface plays a significant role for fabricating devices with high V OC and PCE.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium oxide (VO 2 ) is also an n -type semiconductor with a deep conduction band energy level, making it an appropriate HTL [ 82 , 83 ]. VO x on top of the perovskite layer using a ZrO 2 scaffold resulted in a PCE of 15.8% [ 58 ]. VO x was applied by post-treatment of the perovskite/carbon interface to facilitate the charge transfer from the high work function of VO x while not sacrificing the conductivity of carbon.…”
Section: Device Performance and Stability Of Inorganic Hole Transport Materials-based Pscsmentioning
confidence: 99%
“…Though the mixed halide perovskite resulted in achieving improved device efficiency, its poor stability and degradation phenomena under the ambient environment have been a tailback for the commercial development of long-term stability PSCs [60][61][62] . As to control the degradation of perovskite structure due to moisture, heat, light and ion migrations 63 , several remedial measures have been reported which can make the perovskite structure to withstand under ambient conditions 64 and some of them are like incorporation and post-treatment of perovskite material using inorganic compounds 65 , composition engineering using mixed anions and cations 66 and also by introducing carbon-based materials 60,64 . Hence in the present study, an attempt has been made to overcome the above-mentioned drawbacks by encapsulating the perovskite material using carbon-based materials which could be used as an interfacial layer sandwiched between the active absorber and as prepared graphitic carbon counter electrode.…”
Section: Structural and Morphological Analysis Of The Prepared Ec-gc1mentioning
confidence: 99%